2012
DOI: 10.1002/ejsp.1876
|View full text |Cite
|
Sign up to set email alerts
|

Causal uncertainty during initial interactions

Abstract: Causal uncertainty (CU) refers to persistent doubts people have about their ability to understand causes of social events. Although such confusion about social dynamics should affect social exchanges, previous research has been limited to the realm of social cognition (i.e., computer‐based studies exploring perceptions of hypothetical others). In three studies, we explored CU effects during real‐time social interactions with unacquainted conversational partners. We found that high CU participants perceived the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, Knobloch (2007) also suggested that ''people's doubts about themselves may lead them to feel more insecure about their relationships'' (p. 42), suggesting that people who experience other types of chronic uncertainty might be more likely to experience RU. Although researchers have examined how various types of uncertainty might be related to cognitive and behavioral uncertainty (i.e., doubts about thoughts= feelings, and about how to act=react during social interactions, respectively) during initial interactions (e.g., Boucher & Jacobson, 2012;Douglas, 1994), research has yet to examine the relationship between these dispositional forms of uncertainty and RU.…”
Section: Individual Differences and Rumentioning
confidence: 99%
See 3 more Smart Citations
“…However, Knobloch (2007) also suggested that ''people's doubts about themselves may lead them to feel more insecure about their relationships'' (p. 42), suggesting that people who experience other types of chronic uncertainty might be more likely to experience RU. Although researchers have examined how various types of uncertainty might be related to cognitive and behavioral uncertainty (i.e., doubts about thoughts= feelings, and about how to act=react during social interactions, respectively) during initial interactions (e.g., Boucher & Jacobson, 2012;Douglas, 1994), research has yet to examine the relationship between these dispositional forms of uncertainty and RU.…”
Section: Individual Differences and Rumentioning
confidence: 99%
“…However, more recent research suggests that causally uncertain people experience difficulties reducing their cognitive and behavioral uncertainty during actual social exchanges. For example, Boucher and Jacobson (2012) found that high CU participants reported more doubts about their own thoughts and feelings, as well as about their conversational partner's thoughts and feelings, following a brief interaction with a same-sex stranger. In turn, these doubts led to more negative appraisals of the conversation and conversational partner.…”
Section: Causal Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…However, such a presumption neglects one key aspect of early interactions. Although getting to know another person is often a neutral or slightly positive experience, it can simultaneously be somewhat uncomfortable or awkward, as individuals know little about their interaction counterpart and are unsure about how the interaction will unfold (Berger & Calabrese, 1975; Boucher & Jacobson, 2012; Fraley & Aron, 2004; Graham, 1995). Accordingly, we believe that focusing one’s attention on the social interaction and how one feels about it may actually backfire, increasing rumination over the discomfort and awkwardness associated with the interaction.…”
mentioning
confidence: 99%